Cutaneous Microvascular Blood Flow and Reactivity in Hypoxia - Treml, Benedikt; Kleinsasser, Axel; Stadlbauer, Karl-Heinz; Steiner, Iris; Pajk, Werner; Pilch, Michael; Burtscher, Martin; Knotzer, Hans (Frontiers in Physiology, 2018)
As is known, hypoxia leads to an increase in microcirculatory blood flow of the skin in healthy volunteers. In this pilot study, we investigated microcirculatory blood flow and reactive hyperemia of the skin in healthy subjects in normobaric hypoxia. Furthermore, we examined differences in microcirculation between hypoxic subjects with and without short-term acclimatization, whether or not skin microvasculature can acclimatize. Fourty-six healthy persons were randomly allocated to either short-term acclimatization using intermittent hypoxia for one hour over seven days at an FiO2 0.126 (treatment, n = 23) or sham short-term acclimatization for one hour over seven days at an FiO2 0.209 (control, n = 23). Measurements were taken in normoxia and at 360 and 720 minutes during hypoxia (FiO2 0.126). Microcirculatory cutaneous blood flow was assessed with a laser Doppler flowmeter on the forearm. Reactive hyperemia was induced by an ischemic stimulus. Measurements included furthermore hemodynamics, blood gas analyses and blood lactate. Microcirculatory blood flow increased progressively during hypoxia (12.3 ± 7.1 to 19.0 ± 8.1 perfusion units; p = 0.0002) in all subjects. The magnitude of the reactive hyperemia was diminished during hypoxia (58.2 ± 14.5 to 40.3 ± 27.4 perfusion units; p = 0.0003). Short-term acclimatization had no effect on microcirculatory blood flow. When testing for a hyperemic response of the skin’s microcirculation we found a diminished signal in hypoxia, indicative for a compromised auto-regulative circulatory capacity. Furthermore, hypoxic short-term acclimatization did not affect cutaneous microcirculatory blood flow. Seemingly, circulation of the skin was unable to acclimatize using a week-long short-term acclimatization protocol. A potential limitation of our study may be the seven days between acclimatization and the experimental test run. However, there is evidence that the hypoxic ventilatory response, an indicator of acclimatization, is increased for one week after short-term acclimatization. Then again, one week is what one needs to get from home to a location at significant altitude.